Classic assimilation, self-selection and parent status: An analysis of the central–local political trust among highly educated Mainland migrants in Hong Kong. (March 2023) - Lam, Ka Wang Kelvin; Zhong, Hua; Gu, Gloria Yuxuan
Prior research overlooks highly educated migrants and their political incorporation in host societies. This study applies both classic assimilation and self-selection theories to understand political trust among highly educated migrants from Mainland China in Hong Kong, including their trust toward local (host society) and central (home society) governments. We also address the possibility of selective assimilation adopted by migrant parents as risk-reducing strategies. Based on a survey of highly educated Mainland migrants in Hong Kong ( n = 2, 884), our results show partial support for both theories. Migrants' political trust is influenced by both their post-migration political exposure and their pre-migration political attitudes. Moreover, migrant parents tend to remain bicultural, showing more positive attitudes toward both governments in host and home societies.